Prevalence and risk of skeletal complications and use of radiation therapy in elderly women diagnosed with metastatic breast cancer - Hussain, Arif; Yong, Candice; Tkaczuk, Katherine H. R.; Qian, Yi; Arellano, Jorge; Mullins, C. Daniel; Onukwugha, Eberechukwu (PloS one, 2018)
Real-world data regarding patient factors associated with the occurrence of spinal cord compression (SCC) or pathological fracture (PF), or need for bone surgery (BS), or use of radiation therapy (RAD) (i.e. skeletal complications and radiation therapy; SCRT) are limited for women with metastatic breast cancer (BCa). Given the substantial clinical and economic burden of these events in advanced BCa, we conducted the present study to understand the prevalence and identify the risk factors associated with these events among elderly women presenting with de novo metastatic BCa. Using linked Surveillance, Epidemiology, and End Results and Medicare data, we identified women with incident metastatic BCa diagnosed during 2005-2009. Associations between patient demographics and select clinically relevant factors, and SCRT were examined using the Cox proportional hazards model, accounting for death as a competing risk. Of 3,731 Medicare beneficiaries with incident metastatic BCa, 1,808 (48.5%) experienced at least one SCRT event during a median follow-up of 13.2 months; a majority (69%) experienced a subsequent SCRT event. The proportions of women who had RAD, PF, BS, and SCC were: 32%, 28%, 8%, and 4%. Older women (80+ years), or those with more comorbid conditions (CCI≥2) had a statistically significant lower risk of SCRT (HR 0.78 [CI: 0.67-0.92, p<0.01]; HR 0.77 [CI: 0.67-0.89, p<0.01], respectively), primarily due to lower frequency of radiotherapy (p<0.01). Compared to Caucasians, African Americans had lower risk of SCRT (HR 0.70 [CI: 0.60-0.82, p<0.01]), as well as all SCRT subtypes defining this group except for SCC, which was the same for both race groups. This study highlights that certain patient characteristics and clinical factors are associated with the risk of spinal cord compression or pathologic fractures, or need for bone surgery or radiation among women with metastatic BCa. In future studies, it will also be important to consider the clinical and economic burden based on these components of skeletal complications and radiation therapy use in order to guide and improve the management of women with advanced BCa.